General Construction of 2D Ordered Mesoporous Iron‐Based Metal–Organic Nanomeshes. Issue 37 (9th August 2020) - Ai, Yan; Han, Zhuolei; Jiang, Xiaolin; Luo, Hao; Cui, Jing; Bao, Qinye; Jing, Chengbin; Fu, Jianwei; Cheng, Jiangong; Liu, Shaohua
Abstract: Nanomeshes with highly regular, permeable pores in plane, combining the exceptional porous architectures with intrinsic properties of 2D materials, have attracted increasing attention in recent years. Herein, a series of 2D ultrathin metal–organic nanomeshes with ordered mesopores is obtained by a self‐assembly method, including metal phosphate and metal phosphonate. The resultant mesoporous ferric phytate nanomeshes feature unique 2D ultrathin monolayer morphologies (≈ 9 nm thickness), hexagonally ordered, permeable mesopores of ≈ 16 nm, as well as improved surface area and pore volume. Notably, the obtained ferric phytate nanomeshes can directly in situ convert into mesoporous sulfur‐doped metal phosphonate nanomeshes by serving as an unprecedented reactive self‐template. Furthermore, as advanced anode materials for Li‐ion batteries, they deliver excellent capacity, good rate capability, and cycling performance, greatly exceeding the similar metal phosphate‐based materials reported previously, resulting from their unique 2D ultrathin mesoporous structure. Therefore, the work will pave an avenue for constructing the other 2D ordered mesoporous materials, and thus offer new opportunities for them in diverse areas. Abstract : A general way to construct 2D ultrathin mesoporous metal–organic nanomeshes by self‐assembly is proposed. Employing bioresourced phytic acid as phosphorus source, the product features ultrathin thickness and hexagonally ordered, permeable mesopores as well as excellent electrochemical performance for Li‐ion storage. Notably, serving as a reactive self‐template, they can be directly converted into mesoporous sulfur‐doped nanomeshes.